2016
DOI: 10.1186/s13049-016-0323-3
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial function at the early phase of traumatic brain injury: a prospective controlled study

Abstract: BackgroundThe concept of brain-heart interaction has been described in several brain injuries. Traumatic brain injury (TBI) may also lead to cardiac dysfunction but evidences are mainly based upon experimental and clinical retrospective studies.MethodsWe conducted a prospective case-control study in a level I trauma center. Twenty consecutive adult patients with severe TBI were matched according to age and gender with 20 control patients. The control group included adult patients undergoing a general anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…We used STE, which provides robust and sensitive evaluation of LV function [7,18] and was already studied in SAH patients [8]. Another monocentric pilot study performed in TBI patients also suggested a preserved GLS at baseline [19]. Our data, suggest that stress cardiomyopathy may occur but is not frequent.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We used STE, which provides robust and sensitive evaluation of LV function [7,18] and was already studied in SAH patients [8]. Another monocentric pilot study performed in TBI patients also suggested a preserved GLS at baseline [19]. Our data, suggest that stress cardiomyopathy may occur but is not frequent.…”
Section: Discussionmentioning
confidence: 65%
“…Decompressive craniectomy was performed in 8 (8%) patients, and 27 (27%) patients received pentothal in the ICU. The median duration of mechanical ventilation was 9 [5][6][7][8][9][10][11][12][13][14] days and the mean ICU length of stay was 16 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days. Demographic data and outcome are displayed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Another case-control study of 20 patients with severe TBI also did not find depressed LVEF after a TBI. 5 In a recent prospective study of 32 patients with moderate to severe TBI, the study investigators performed echocardiograms within a day of TBI and followed up with repeat echocardiogram twice after the initial study, over the course of 7-9 days. 4 Seven out of 32 (22%) patients in that study with moderate to severe TBI developed LV systolic dysfunction, and the LV systolic function recovered within one week.…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of cardiac dysfunction after TBI varied significantly among existing studies, ranging from 0% to 50%. [3][4][5][6]13,14 This discrepancy could be attributed partly to differences in the study design, sample size, heterogeneity in the definition of cardiac dysfunction and differences in the methods of estimating left ventricular systolic function. Two studies from single institution reported that 22% of patients with TBI had evidence of cardiac dysfunction, despite significant differences in the study design, age of the patient population, severity of TBI and echocardiographic methods for estimating LV systolic function (Simpson's method versus fractional shortening).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation